P32 25 year experience of cardiac tumours at a tertiary paediatric cardiology centre. (2nd March 2016) - Ramcharan, Tristan; Wasala, Desha; Seager, Ezgi; Chikermane, Ashish; Chaudhari, Milind
Abstract : Background: Primary cardiac tumours are rare with an incidence of around 1 in 5000, 1 with literature showing that the majority are benign rhabdomyomas and present under 1 year of age. 2 The most common co-morbidity with rhabdomyomas is Tuberous Sclerosis (TS). Aim: We present our experience of cardiac tumours at a single tertiary cardiac centre over 25 years, looking at presentation and outcomes. Method: A retrospective review of all patients <16 years with a primary cardiac tumour between 1990–2015. 15 patients were excluded (non-cardiac primary tumours), leaving 49 patients. Results: Of the 48 patients, 18 (36%) were diagnosed in the neonatal period (6 antenatal, 12 postnatal). Median age at presentation of the other 31 patients was 18 months. The most common reasons for presentation was during routine TS Screening (38%), and detection of a murmur (14%). Tumour classification was based on clinical features and imaging. There were 38 rhabdomyomas (4 excised with histological confirmation), 5 fibromas (all excised with histological confirmation), and 5 myxomas (4 excised with histological confirmation). In the rhabdomyoma group, 18 patients had multiple tumours (47%) with an average of 3 cardiac tumours each. Echocardiogram was done in all patients, 24 h tapes on 15 patients of which 13 were in cases of rhabdomyoma and 2 in fibromas, with cardiac MRI done in 2 patients. The location for tumours was right ventricle (39%), left ventricle (33%) and ventricular septum (20%). In the rhabdomyoma group 76% were also diagnosed with tuberous sclerosis. Eight patients had other cardiac lesions, with 6 having minor shunts (ASD/VSD/PDA) Arrhythmias were detected in only 5 patients, 3 in fibromas (60% of fibromas) and 2 with rhabdomyomas. Management was predominantly conservative. The majority of rhabdomyomas regressed in size (86%) with the remainder staying the same or growing proportionally, and these all remain under medical follow-up. Thirteen patients were lesion free at median 5 years, 4.5 years from diagnosis.  13 patients had surgical excision, 8 due to outflow obstruction and 3 due to the patient presenting with stroke. None of the rhabdomyomas recurred, but 2 fibromas and 2 myxomas recurred and these required further excision (on average 3 times). No patient died as a result of their cardiac tumour. In our series, 27% of patients had surgery, 6% had an episode of arrhythmia and 4% required anti-arrhythmics. From a cardiac perspective, 73% of patients were asymptomatic. Conclusions: The majority of cardiac tumours do not need intervention. Monitoring for lesion progression and arrhythmia is essential. The most common primary cardiac tumour is rhabdomyoma, the main associated condition is tuberous sclerosis.